Pengaruh Literasi Keuangan, Teman Sebaya, dan Gaya Hidup Terhadap Perilaku Konsumtif Mahasiswa Rantau di Kota Singaraja - Ni Kadek Rarasawitri; I Nyoman Sujana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2026)
The phenomenon of consumptive behavior can be found among out-of-town students because they live far from their parents, thus requiring them to manage their finances independently. This study aims to examine the influence of financial literacy, peers, and lifestyle on the consumptive behavior of out-of-town students in Singaraja City. This research uses a quantitative approach with a causal research type. The population of this study is out-of-town students in Singaraja City with a sample size of 85 people. Data were collected through distributing questionnaires via Google Form, the data analysis technique used was multiple linear regression analysis using IBM SPSS statistics version 26. The results of the study show (1) there is a positive and significant influence of financial literacy on the consumptive behavior of out-of-town students partially. (2) there is a positive and significant influence of peers on the consumptive behavior of out-of-town students partially. (3) there is a positive and significant influence of lifestyle on the consumptive behavior of out-of-town students partially. (4) there is a positive and significant influence of financial literacy, peers, and lifestyle on the consumptive behavior of out-of-town students simultaneously.